2023
DOI: 10.15503/jecs2023.2.78.92
|View full text |Cite
|
Sign up to set email alerts
|

The Philosophical Context of Curriculum Innovations with a Focus on Competence Development

Peter Kondrla,
Radoslav Lojan,
Patrik Maturkanič
et al.

Abstract: Aim. The article describes the philosophical background of competency education and analyses the weaknesses that are present in curriculum changes, focusing on the absence of dynamic acceptance of otherness. Concept. The starting point is a reflection on the philosophical background of education as a repetition and production of the same. The basic principles of the post-metaphysical approach of education to otherness and the interpretation of the innovation curriculum in relation to these principles are prese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…Pedagogical Diplomacy II universities. One of the major shortcomings of the current pre-graduate training of student teachers, in agreement with Hermochová (2010), is the fact that not all higher education institutions involved in the preparation of future teachers of regional education (primary and lower and upper secondary level of education) have incorporated into the relevant part of the curricula the area of acquiring specific competences of a form teacher at such a level, as the requirements of practice would require (Kondrla et al, 2023). In the context of the above, a grant project is being carried out at the Faculty of Education of Comenius University, the aim of which is to innovate the curricula of the relevant part of the study programs of the undergraduate preparation of future teachers so that the graduates of teacher study programs would be better prepared for specific situations related to the key competences of a form teacher in primary and secondary schools.…”
Section: Jg (2024) Sonderausgabementioning
confidence: 84%
“…Pedagogical Diplomacy II universities. One of the major shortcomings of the current pre-graduate training of student teachers, in agreement with Hermochová (2010), is the fact that not all higher education institutions involved in the preparation of future teachers of regional education (primary and lower and upper secondary level of education) have incorporated into the relevant part of the curricula the area of acquiring specific competences of a form teacher at such a level, as the requirements of practice would require (Kondrla et al, 2023). In the context of the above, a grant project is being carried out at the Faculty of Education of Comenius University, the aim of which is to innovate the curricula of the relevant part of the study programs of the undergraduate preparation of future teachers so that the graduates of teacher study programs would be better prepared for specific situations related to the key competences of a form teacher in primary and secondary schools.…”
Section: Jg (2024) Sonderausgabementioning
confidence: 84%
“…SEL is defined as "the process through which all young people and adults acquire and apply the knowledge, skills, and attitudes to develop healthy identities, manage emotions and achieve personal and collective goals, feel and show empathy for others, establish and maintain supportive relationships, and make responsible and caring decisions" [1][2][3]. SEL promotes attention to students' emotional and social needs, respect for their individuality and differences, and the development of their self-awareness and social skills, which is consistent with competency-oriented pedagogy and education in the concept of postmetaphysical thinking [4,5]. Research has found that social and emotional competence can predict a child's mental health [6], while a lack of such competence is strongly associated with behaviors such as suicide, as poor behavioral and emotional control is the leading cause of death among adolescents [7].…”
Section: Introductionmentioning
confidence: 89%